Conversations About Science Advocacy: A March for Science Perspective. (27th February 2019) - Weinberg, C K; Gunther, K E; Davidson, J; Grover, V; Sasse, S F; Yang, A
Abstract: The 2017 and 2018 Marches for Science were landmark events that brought together people around the world in support of science. The March for Science built a coalition between scientists and the science-supporting public that helped to expand the voices and perspectives in the science advocacy movement. That collaboration that has continued to power science advocacy long past a 1-d event. In this paper, organizers of the Washington, DC; San Francisco, CA; and Madison, WI marches and staff of the March for Science organization reflect on the collaborative nature of science advocacy and the March for Science movement and its role and future in the science advocacy space.